ADOS-Eye-Tracking: The Archimedean Point of View and Its Absence in Autism Spectrum Conditions - Schaller, Ulrich Max; Biscaldi, Monica; Burkhardt, Anna; Fleischhaker, Christian; Herbert, Michael; Isringhausen, Anna; Tebartz van Elst, Ludger; Rauh, Reinhold (Frontiers in Psychology, 2021)
Face perception and emotion categorization are widely investigated under laboratory conditions that are devoid of real social interaction. Using mobile eye-tracking glasses in a standardized diagnostic setting while applying the Autism Diagnostic Observation Schedule (ADOS‑2), we had the opportunity to record gaze behavior of children and adolescents with and without ASD during social interaction. The objective was to investigate differences in eye-gaze behavior between three groups of children and adolescents either (1) with high-functioning ASD, or (2) with unconfirmed diagnosis of ASD, or (3) with typical development during social interaction with an adult interviewer in a diagnostic standard situation using the ADOS‑2. In a case control study, we used mobile eye-tracking glasses in an ecologically valid and highly standardized diagnostic interview to investigate suspected cases of ASD. After completion of the ASD diagnostic gold standard, the participants were assigned to two groups based on their diagnosis (ASD vs. Non-ASD) and compared with a matched group of neurotypically developed controls. The primary outcome measure is the percentage of total dwell times assessed as different areas of interest (AOIs) with regard to the face and body of a diagnostic interviewer and the surrounding space. Overall, 65 children and adolescents within an age range of 8;3 yrs to 17;9 yrs were included in the study. The data revealed significant differences, especially in the central-face area. Previous investigations under laboratory conditions gave preferential attention to the eye region during face perception to describe differences between ASD and NTD. In this study—using an ecologically valid setting within a standard diagnostic procedure—the results indicate that typically developed controls seem to process faces and facial expressions in a holistic manner originating from the central-face region. Conversely, participants with ASD seem to avoid the central-face region and show unsystematic gaze behavior, not using the preferred landing position in the central-face region as the Archimedean point of face perception.